2022
DOI: 10.48550/arxiv.2203.03637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Terrestrial volcanic eruptions and their association with solar activity

Abstract: We compare the frequencies of volcanic eruptions in the past 270 years with the variations of solar activity and summary curve of principal components of the solar background magnetic field (SBMF) derived from the WSO synoptic magnetic maps. Quartile distributions of volcanic eruption frequencies over the four phases of a 11 year cycle (growth, maximum, descent and minimum) reveal higher numbers of eruptions occurring at the maxima of SBMF of southern polarity with some increases at the minima of sunspot numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Vasilieva & Zharkova found that volcanic eruption from the past for 270 years ago with the variations of solar activity and summary curve of principal components of the solar background magnetic field. They obtained a dominant 22-year period of volcanic activity and a weaker peak of 10.7 years [10]. Volcanoes and seasonal variations are studied in several papers, one by Mason et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…Vasilieva & Zharkova found that volcanic eruption from the past for 270 years ago with the variations of solar activity and summary curve of principal components of the solar background magnetic field. They obtained a dominant 22-year period of volcanic activity and a weaker peak of 10.7 years [10]. Volcanoes and seasonal variations are studied in several papers, one by Mason et al [11].…”
Section: Introductionmentioning
confidence: 99%